Formation of assimilable organic carbon (AOC) during drinking water disinfection: A microbiological prospect of disinfection byproducts - Guocheng Huang; Tsz-Wai Ng; Huan Chen; Alex T. Chow; Shengwei Liu; Po Keung Wong (Environment International, 2020)
Disinfection processes might alter the chemical structure of biological recalcitrant natural organic matter (NOM) in source water to form assimilable organic carbon (AOC), which can be readily utilized by microbes for growth. However, AOC has not been classified as disinfection byproducts (DBPs) before and little is known about the chemical and structural nature of AOC. This study, for the first time, considers the disinfection-induced AOC as DBPs from a microbiological perspective. The AOC formation by three types of disinfection processes, i.e., chlorination, UVC irradiation (254 nm) and photocatalysis represented by TiO2-UVA in drinking water containing two reference NOM materials of Suwannee River and Nordic Reservoir (SRNOM and NRNOM, respectively) were comparatively benchmarked using Pseudomonas aeruginosa as inoculum. Results showed that chlorination caused a substantial increase in AOC content, whereas TiO2-UVA led to a moderate increase in AOC content and UVC rendered the AOC content unchanged, independent of the types of NOM. Molecular weight indicated by spectral slope ratio and fluorescence fingerprint were found to not provide critical information about the AOC formation potential. FTIR and FT-ICR-MS results indicated that the AOC formation by chlorination was attributed to the oxidation and chlorine substitution on aromatic molecules to form molecules with carboxylic- and alcohol- functionalities, as well as chlorinated aromatics. These molecules could be metabolized and assimilated by Pseudomonas species by a catechol pathway. The results obtained in this study can provide valuable insight regarding the selection of proper technologies for disinfection to prevent microbial growth/regrowth in the distributing system and is intended to encourage more thinking and research on AOC as a new prospect of DBPs during disinfection of drinking water. Keywords: Drinking water, Natural organic matter, Assimilable organic carbon, Microbial regrowth, Disinfection byproducts